2004
DOI: 10.1038/sj.bjp.0706012
|View full text |Cite
|
Sign up to set email alerts
|

Kinin B1 receptors: key G‐protein‐coupled receptors and their role in inflammatory and painful processes

Abstract: Kinins are a family of peptides implicated in several pathophysiological events. Most of their effects are likely mediated by the activation of two G-protein-coupled receptors: B 1 and B 2 . Whereas B 2 receptors are constitutive entities, B 1 receptors behave as key inducible molecules that may be upregulated under some special circumstances. In this context, several recent reports have investigated the importance of B 1 receptor activation in certain disease models. Furthermore, research on B 1 receptors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
201
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(215 citation statements)
references
References 177 publications
(272 reference statements)
10
201
0
4
Order By: Relevance
“…These observations have been explained through receptor coupling to different second messenger pathways in different cells and/or to the presence of different regional profiles of receptor subtype expression [1,17]. In mammals, including humans, the primary structure of BK appears to be invariant as is the presence of two different subtypes of BK receptors, designated B 1 and B 2 [14,15] and both are classical, seven trans-membrane domain, G-protein-linked receptors (GPCRs) [2,11,14,15]. The B 2 receptor is constitutively expressed by many types of cells, including smooth muscle cells, while the B 1 receptor is inducible and is expressed de novo in various cell types after trauma or at sites of chronic inflammation [2,11,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These observations have been explained through receptor coupling to different second messenger pathways in different cells and/or to the presence of different regional profiles of receptor subtype expression [1,17]. In mammals, including humans, the primary structure of BK appears to be invariant as is the presence of two different subtypes of BK receptors, designated B 1 and B 2 [14,15] and both are classical, seven trans-membrane domain, G-protein-linked receptors (GPCRs) [2,11,14,15]. The B 2 receptor is constitutively expressed by many types of cells, including smooth muscle cells, while the B 1 receptor is inducible and is expressed de novo in various cell types after trauma or at sites of chronic inflammation [2,11,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, including humans, the primary structure of BK appears to be invariant as is the presence of two different subtypes of BK receptors, designated B 1 and B 2 [14,15] and both are classical, seven trans-membrane domain, G-protein-linked receptors (GPCRs) [2,11,14,15]. The B 2 receptor is constitutively expressed by many types of cells, including smooth muscle cells, while the B 1 receptor is inducible and is expressed de novo in various cell types after trauma or at sites of chronic inflammation [2,11,14,15]. Each receptor has different ligand structure/activity requirements with BK activating both but with des-(Arg 9 )-BK being the preferential ligand for the B 1 subtype [2,11,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, a number of studies have shown the increased expression of B1R and B2R in atherosclerotic vessels and peripheral blood cells of patients with atherosclerosis (11,12). Particularly, in the cardiovascular systems, kinins have been found to be involved in the pathogenesis of heart failure (13).…”
Section: Introductionmentioning
confidence: 99%